Electrical and rheological characterization of poly(trimethylene terephthalate) hybrid nanocomposites filled with COOH functionalized MWCNT and graphene nanosheets. Issue 8 (7th February 2017) - Paszkiewicz, S.; Szymczyk, A.; Kasprowiak, I.; Zenker, M.; Pilawka, R.; Linares, A.; Ezquerra, T. A.; Rosłaniec, Z.
Abstract : Poly(trimethylene terephthalate) (PTT) composites filled with well‐dispersed functionalized multi‐walled carbon nanotubes (MWCNT‐COOH) and graphene nanosheets (GNS) were prepared through in situ polymerization. The effect of increased nanotubes and nanosheets concentration on the electrical conductivity and rheological behavior was investigated. The electrical conductivity increased by about ten orders of magnitude for PTT/MWCNT‐COOH/GNS composites with 0.4 wt% of MWCNT‐COOH and 0.3 wt% of GNS content. For insulating hybrid polymer nanocomposites, with a MWCNT‐COOH content ≤ 0.2 wt%, GNS produces a synergic effect by acting as junction additive for MWCNT leading to additional conductive pathways. However, for hybrid nanocomposites with 0.4 wt% of MWCNT‐COOH further addition of GNS caused only slight improvement in electrical conductivity. Additionally, rheological analysis confirmed interconnected or network‐like structures formed as a result of nanofiller‐nanofiller and nanofiller‐polymer interactions. POLYM. COMPOS., 39:2961–2968, 2018. © 2017 Society of Plastics Engineers